New plant associations for Monalonion velezangeli (Hemiptera: Miridae) in green urban areas of Bogotá (Colombia) (2018)
Monalonion velezangeli Carvalho and Costa (Hemiptera: Miridae) is a polyphagous plant bug recognized as one of the most important pest species of coffee and avocado in rural regions of Colombia. M. velezangeli is reported for the first time in green urban areas in the high Andean city of Bogotá (Colombia). Specimens were collected on eight species of urban trees planted in the city, of which five represent new plant associations for M. velezangeli. The plant species Schinus molle L. (Anacardiaceae) is for the first time reported as new host plant damaged by M. velezangeli under urban conditions.